Ruyiping formula inhibits metastasis via the microRNA-134-SLUG axis in breast cancer - Ziwei Jiang; Lixia Pei; Ying Xie; Qun Ye; Xiaoqiang Liang; Yiyi Ye; Sheng Liu (BMC, 2021)
Abstract Background Metastasis is the leading cause of death among breast cancer patients. MicroRNA-134 has been reported to have a tumor-suppressive role in breast cancer. Ruyiping (RYP), a traditional Chinese formula, has been shown with the ability to reduce breast cancer metastasis in pre-clinical studies. This present study was designed to examine whether miR-134 was involved in RYP-inhibited breast cancer metastasis. Methods The expression of SLUG, E-Cadherin, N-Cadherin and miR-134 in MDA-MB-231 and 4 T1 cells treated with RYP or vehicle control were determined by quantitative realtime-PCR and western blot. Invasiveness determined by transwell assay as well as SLUG gene expression determined by qPCR were detected in cells transfected with chemically synthesized miR-134 mimics or inhibitors. BALB/c mice were injected with 4 T1 cells orthotopically and fed with RYP through gavage. Breast tumor growth, metastasis and tumor expression of EMT markers were detected. Results Compared with the control, Ruyiping formula significantly inhibited SLUG-regulated breast cancer cells invasion. MiR-134 was induced by RYP in vitro and in vivo and was able to suppress SLUG by targeting its 3'UTR. RYP suppressed SLUG expression and cell invasion through miR-134. In 4 T1 tumor-bearing mice, RYP significantly inhibited 4 T1 tumor growth and lung metastasis, increased the levels of miR-134 and epithelial marker while decreased the levels of SLUG and mesenchymal marker. Conclusion Our data uncovered that Ruyiping formula exerts an anti-metastatic activity against breast cancer cells by regulating SLUG through miR-134. MiR-134-SLUG axis might be a promising strategy in breast cancer therapy.